2006
DOI: 10.1111/j.1365-2583.2006.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate responses of transcription factors to ecdysone during programmed cell death in the anterior silk gland of the silkworm, Bombyx mori

Abstract: Programmed cell death (PCD) in Bombyx mori anterior silk glands (ASGs) is triggered by 20-hydroxyecdysone (20E). We examined the expression profiles and effects of 20E on 11 transcription factor genes in the fifth instar to determine whether they demonstrate the hierarchical control seen in Drosophila PCD. Results indicate that EcR-A and usp-2 , but not EcR-B1 or usp-1 , may be components of the ecdysone receptor complex. Up-regulation of E75A, BHR3 , and three BR-C isoforms, but not E75B , appeared to be asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 45 publications
(72 reference statements)
1
49
1
Order By: Relevance
“…34 A balancing crosstalk occurs between autophagy and caspase activity in the remodeling fat body, as the inhibition of autophagy induces caspase activity and the inhibition of apoptosis induces autophagy. 35,36 During Bombyx metamorphosis, autophagy and apoptosis occur simultaneously in the silk gland, 37,38 and fat body. 28,29,39 Importantly, we found that autophagy precedes apoptosis in the midgut.…”
Section: Basic Research Papermentioning
confidence: 99%
See 2 more Smart Citations
“…34 A balancing crosstalk occurs between autophagy and caspase activity in the remodeling fat body, as the inhibition of autophagy induces caspase activity and the inhibition of apoptosis induces autophagy. 35,36 During Bombyx metamorphosis, autophagy and apoptosis occur simultaneously in the silk gland, 37,38 and fat body. 28,29,39 Importantly, we found that autophagy precedes apoptosis in the midgut.…”
Section: Basic Research Papermentioning
confidence: 99%
“…The cells were subsequently incubated with 10 mL of 10 mg/mL RNase A (TIANGEN, M1105) at 37 C for 1 h. Then, 10 mL of 20 mg/mL protease K (TIANGEN, K0012) was added to the reaction for further incubation overnight at 55 C. The following DNA extraction steps were performed according to the method used in silkworm midguts. 40 Finally, 10 mg of genomic DNA was detected on a 2.5% agarose gel and visualized by staining with ethidium bromide.…”
Section: Dna Ladder Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Ec is responsible for embryo development, larval molts, pupation, and metamorphosis in Drosophila, Bombyx mori and other arthropods (Riddiford 1993, Subramoniam 2000, Sekimoto et al 2006. The Ec is known to regulate a number of biological processes by coordinating with juvenile hormone (JH; Dubrovsky 2005) and cross talk between them has been reported in Daphnia and other arthropods (Mu & LeBlanc 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Metamorphosis of holometabolous insects carries a radical reconstruction of the body planes to a replacement of the larval tissues by adult tissues and structures. Processes that drive these changes are controlled by the insect steroid molting hormone ecdysone (Jiang et al, 1997(Jiang et al, , 2000Sekimoto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%